The Role of the Sahabat Bencana Website in Strengthening Village Resilience: An Analysis of the Utilization of Disaster Information in Forming Disaster-Resilient Villages in Pasaman Barat Regency - Ferdi Wardana; Abdul Wahab; Wadi Murbarok (International Journal of Scientific Research, 2024)
Indonesia, as the largest archipelagic country in the world, faces significant natural disaster risks due to its geographic location between three major tectonic plates. West Sumatra Province, particularly Pasaman Barat Regency, is a high-risk area for disasters such as flash floods, exacerbated by geographical conditions, high rainfall intensity, and spatial planning violations. This study aims to design and evaluate flood disaster management strategies through the utilization of information from the internet, particularly via the "Sahabat Bencana" website. A qualitative approach with descriptive methods was employed in this research. Data were collected through interviews, observations, and document studies, and analyzed using strategy theory. The results indicate that the "Sahabat Bencana" website can be an effective tool in forming Disaster-Resilient Villages by providing up-to-date information, early warnings, and mitigation steps. However, its effectiveness is influenced by digital literacy, information technology infrastructure, and content relevance. Challenges in implementing this website include low digital literacy, limited internet access, and socio-cultural factors. Therefore, improving digital literacy, providing adequate infrastructure, and involving community leaders in website socialization are necessary. Overcoming these challenges will maximize the effectiveness of the "Sahabat Bencana" website in strengthening village resilience against disasters in Pasaman Barat Regency and other regions in Indonesia.